Suicidality and social problem‐solving skills among individuals with first‐episode psychosis participating in Coordinated Specialty Care. Issue 3 (14th April 2020) - Breitborde, Nicholas J. K.; Wastler, Heather; Pine, Jacob G.; Moe, Aubrey M.
Abstract: Aim: Although suicidal ideation may decrease over the course of participation in specialized clinical programmes for first‐episode psychosis (FEP), it is unclear whether such improvements exceed those that occur during treatment as usual. Clarifying the mechanisms underlying reductions in suicidal ideation and behaviour among individuals with first‐episode psychosis may highlight important strategies through which specialized clinical programmes can increase the potency of their services to reduce suicidality among this high‐risk population. Thus, the goal of this study is to evaluate the longitudinal relationships between suicidality and social problem‐solving skills among individuals with FEP participating in Coordinated Specialty Care. Methods: Within‐subject mediational and moderational models were applied to explore the interrelationships and longitudinal course of suicidality, social problem‐solving and duration of untreated psychosis (DUP). Results: Over the first 6 months of care, individuals with FEP experienced improvements in social problem‐solving skills that were found to mediate concurrent reductions in suicidality. Although longitudinal changes in social problem‐solving skills were moderated by DUP, these results should be interpreted cautiously as they may stem in part from a relatively limited number of participants with longer durations of illness. Conclusions: Improvements in social problem‐solving skills during participation in CSC may facilitate reductions in suicidality. Treatments targeting suicidality among individuals with FEP may thus benefit from working to enhance social problem‐solving skills among these individuals. Further research is needed to clarify if and how DUP may influence the magnitude of change in social problem‐solving skills during participation in CSC.